Public scholarship and the evidence movement: understanding and learning from Belgian drug policy development - Tieberghien, Julie (European journal of criminology, 2018)
Debates about public scholarship have gathered momentum in several fields including sociology and criminology. There is much debate over the nature of public scholarship and the forms it can take. In criminology one of the most influential analyses of public scholarship has been developed by Loader and Sparks. For these two thinkers part of the task of scholarship is to contribute to better ‘politics’. In their hands, public criminology is close to another long-running analytical trend – research utilization. The two literatures have for the most part remained separate. This paper puts Loader and Sparks’ framework of public scholarship to the empirical test to see if and how it contributes to understanding the role and nature of evidence use in highly sensitive policy areas. We do this through an analysis of recent changes in Belgian drug policy. We conclude that the framework of Loader and Sparks, although useful in illuminating how publicly engaged scholars can influence and mobilize more open and better-informed public and political debate, is hamstrung by its concentration on the action of individuals in isolation from the complex power structures that underpin the policy process. Synthesizing lessons drawn from the research utilization literature with the work of public criminology provides a potential way forward in understanding the role of evidence in policy and also producing ‘better’ politics in this context.